Persistent Pneumothorax in Neurofibromatosis Type-1 - Hustorio Aliongko Simamora; Susanthy Djajalaksana; Iin Noor Chozin; Dini Rachma Erawati; Hendy Setyo Yudhanto; Gracelia Ruth Elisabeth Damanik; Adinda Amalia Dani; Aditya Sri Listyoko (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Neurofibromatosis type 1 (NF-1) is a rare autosomal dominant disorder. While typically recognized by its cutaneous features, pulmonary involvement, including apical cysts and basal interstitial fibrosis consistent with interstitial lung disease (ILD), can occur in up to 20% of patients. These manifestations create a predisposition to complications such as spontaneous pneumothorax. While this is relatively uncommon, occurring in approximately 1.5% of patients with NF-1, it represents a serious and potentially life-threatening complication when it does occur. Case: A 52-year-old male with a 20-pack-year smoking history and active pulmonary tuberculosis (TB) presented with acute chest pain and dyspnea. Dermatological examination and skin biopsy confirmed the diagnosis of NF-1. A high-resolution computed tomography (HRCT) scan of the chest revealed multiple subpleural pulmonary cysts consistent with NF-1-related ILD, alongside findings suggestive of active TB. The patient was diagnosed with a secondary spontaneous pneumothorax (SSP), which proved to be persistent despite initial chest tube drainage, ultimately requiring surgical intervention. Conclusion: This case highlights that NF-1 is a significant underlying risk factor for persistent pneumothorax, particularly when co-existing with other conditions like active TB and a history of smoking. The chronic inflammation and parenchymal destruction associated with these comorbidities can exacerbate the inherent structural lung abnormalities in NF-1, leading to complex, difficult-to-manage clinical scenarios. Early recognition of pulmonary manifestations in patients with NF-1 is crucial for anticipating and managing severe complications.